Bridging the gap: Microfluidic devices for short and long distance cell-cell communication - Vu, Timothy Quang (Lab Chip, 2017)
Cell-cell communication is a crucial component of many biological functions. For example, understanding how immune cells and cancer cells interact, both at the immunological synapse and through cytokine secretion, can help us understand and improve cancer immunotherapy. The study of how cells communicate and form synaptic connections is important in neuroscience, ophthalmology, and cancer. But in order to increase our understanding of these cellular phenomena, better tools need to be developed that allow us to study cell-cell communication in a highly controlled manner. Some technical requirements for better communication studies include manipulating cells spatiotemporally, high resolution imaging, and integrating sensors. Microfluidics is a powerful platform that has the ability to address these requirements and other current limitations. In this review, we describe some new advances in microfluidic technologies that have provided researchers with novel methods to study intercellular communication. The advantages of microfluidics have allowed for new capabilities in both single cell-cell communication and population-based communication. This review highlights microfluidic communication devices categorized as “short distance,” or primarily at the single cell level, and “long distance,” which mostly encompasses population level studies. Future directions and translation/commercialization will also be discussed.